2022
DOI: 10.1063/5.0118581
|View full text |Cite
|
Sign up to set email alerts
|

The features of surface charging on rectangle mask holes in plasma etching

Abstract: In the plasma etching technique, acquiring a high-quality transfer from the mask pattern onto the substrate under the suppression of the charging effects is of great significance. Most previous publications only focus on studying the charging phenomena on round mask holes. This work shifted the target to an isolated rectangle mask hole and two types of mask arrays (quadrangle and hexagonal arrays). A classical particle simulation program was used. This study first shows that rectangle holes with various ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Correspondingly, the opening displays a non-uniform evolution as shown in figure 1(b). In fact, the corner effect has already been investigated in our recently published literature [10] which takes a series of rectangle mask holes with different ratios of length (L) and width (W d ) as the target. It has been concluded that the corner effect is tightly relevant to the L: W d .…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the opening displays a non-uniform evolution as shown in figure 1(b). In fact, the corner effect has already been investigated in our recently published literature [10] which takes a series of rectangle mask holes with different ratios of length (L) and width (W d ) as the target. It has been concluded that the corner effect is tightly relevant to the L: W d .…”
Section: Introductionmentioning
confidence: 99%